Antimicrobial capacity is related to body colouration and reproductive success in female spotless starlings. (19th September 2020) - Ruiz‐Rodríguez, Magdalena; Azcárate‐García, Manuel; Ruiz‐Castellano, Cristina; Tomás, Gustavo; Díaz‐Lora, Silvia; Pérez‐Contreras, Tomás; Soler, Juan J.
Abstract : Pathogenic microorganisms select for a plethora of defensive mechanisms on their hosts. In males of some species, flashy traits might signal antimicrobial capacity and, thus, they might be favoured in scenarios of sexual selection. Antimicrobial capacity of individuals may predict reproductive success in males, and it could be adapted to changing environments. However, evidence for these associations is still scarce in females. Here, we evaluated antimicrobial capacity of spotless starling Sturnus unicolor females during the mating and nestling–provisioning phase. We did this by measuring 1) the blood plasma inhibition capacity against 12 bacterial strains (antagonistic index), 2) the constitutive innate humoral immunity (lysis and agglutination capacity, a non‐specific first barrier of protection of hosts against microbial parasites) and 3) the uropygial gland size and volume of secretion produced, relevant traits in the protection against, among others, feather‐degrading bacteria. We also measured colouration of throat and back feathers, and of leg and beak integuments. This information was collected during the pre‐laying and nestling stages to compare values from these two periods. We found an increase in the plasma antagonistic index from the pre‐laying to the nestling period, while a decrease on the plasma capacity of agglutination of foreign antigens. Both plasma antagonistic index and humoral immune response measured before breeding were positively related to future female reproductive success. In addition, the level of antimicrobial capacity was related to colouration of leg skin and beak integuments and of back feathers. These associations suggest that, similar to males, females might show through their physical appearance their capacity to fight microbial infections; information that could be evaluated by their potential partners and by female competitors.